Analysis of Children’s Language Ability In Pematang Serai Village Related to The Quality of Child Human Resources From Early - Rusyda Nazhirah Yunus; Munisa Munisa (Universitas 17 Agustus 1945 Semarang, 2023)
Based on initial observations made by researchers in Pematang Serai Village, some children had difficulty speaking because they were still used to the language used in the family environment, and it was difficult to listen to what other people were saying other than using their mother tongue. For example, some children still use their mother tongue or are carried away by the language used at home when they want to ask others for help, which is sometimes difficult to understand. Another problem faced by the people of Pematang Serai Village is moral degradation. Low levels of education and interest in reading are suspected to be the cause of the decline in the character values of the millennial generation. Data analysis was adjusted to the problem formulation questions to be investigated using a quantitative descriptive method that processes numerical data into words, then changes recorded data from interviews. There is an influence of mother tongue on the listening ability of children aged 4-5 years in Pematang Serai Village, the influence of mother tongue on the listening ability of children aged 4-5 years in Pematang Serai Village is 27.8%, and the rest is influenced by cultural factors, community environment and intensity social interaction of 72.2%.